The effect of learning program in developing some social concepts for nursery kids about ( 4 – 5 ): The effect of learning program in developing some social concepts for nursery kids about ( 4 – 5 ) (Journal of the College of Education for Women, 2019)
Abstact:Nursery is one of educational institution in the process of developing thesocial concepts that it includes a quirking the knowledge and experiences thathelp the kid to adjust with environment through arrangement words ,movements and concrete things which are transferred to the kids so as torealize these concepts .Social concepts are numbers of words and statements with social naturewhich the kids learn through the family or nursery in order to effect theireducational style of independent and helping the others .The re searcher adopted this theory because of the little studies in thefiled of social concepts in the nursery.The aims of the study are as following :1- building tools for measuring the social concepts for the nursery kids .2- building educational program for developing some social concepts .3- finding out the effect of some learning programs in developing somesocial concepts for nursery kid such as the concepts of respect cleaning andsystem .From the third aim the following null hypo thesis is posed .There are no differences between the means of control and experimentalgroups.The study is limited on studying social concept for nursery kids in theapplication nursery at AL- Jaderia in 2008 – 2009 for male and female .The sample is ( 20) kids , (10) for experimental group and (10) for control oneThe results of the study show that there are differences for the experimentalgroup .